Exploring Behaviour Management Strategies Used By Teachers In Thailand Primary Schools - Nasiru, Mufutau Afolabi (2019)
This study aimed t o explore the behaviour management strategies used by teachers in Thailand primary schools and the teachers’ perceptions of the effectiveness of their strategies. A five-part questionnaire, comprising - Participants’ Background Information, Behaviour Management Strategies, and Perceptions of Effectiveness of the strategies was completed by 50 teachers from 10 schools. Descriptive statistics, t-tests, and ANOVA were used to analyse the data. The results showed that most teachers used non-aversive behaviour management strategies. The teachers also rated non-aversive strategies as more effective. The study recommends further professional training for teachers, and implementation of Positive Behaviour Support (PBS) in a school-wide approach.